Genetics of some quantitative traits of the rice hybrid CR-1009 (SUB-1) × Novator - P. I. Kostylev; Е. V. Krasnova (Зерновое хозяйство России)
Quantitative traits which are characterized by a wide range of variability in different locations are of great importance for productivity formation. They are plant height, panicle length, number of spikelets and kernels per panicle, 1000-kernel weight, etc. The study of genetic basis of quantitative traits of rice, which are the main elements of yield structure, is an important problem and its solution is necessary to speed up breeding process. The article deals with the establishing of inheritance type, quantity of allelic variants of genes, which participate in determination of some quantitative traits of the rice hybrid obtained from hybridization of the varieties “CR-1009 (Sub-1)” and “Novator”. The genetic analysis of trait splitting has been carried out by the computer program “Polygen A”. The inheritance of the trait “plant height” occurred was of the type of incomplete domination of large values of the trait, the parental forms varied in two pairs of genes. By the panicle length, monogenic differences of the crossed varieties were observed. According to the number of spikelets per panicle, full dominance of the greater value of the trait was identified. The interaction of two genes was identified, with each parental form having both recessive and dominant alleles, but in different loci. Estimating number of kernels per panicle, there were allelic differences in two loci and trait splitting was in a ratio of 9 : 6 : 1. Trait splitting along the length and width of the spikelet was transgressive and was characterized by the dominance of smaller values of the trait. According to 1000-kernel weight, incomplete dominance of smaller values of the trait and monogenic differences of the initial parental forms have been established. According to kernel weight per panicle, the digenous differences of the parental forms and the splitting in a ratio of 15 : 1 were identified. The information that differences are determined by two pairs of main genes can be used in practical breeding. It will allow reducing the amount work to obtain recombinants with the desired combination of characteristics.